Haemostatic devices in parotid surgery: a systematic review. Issue 10 (23rd October 2021) - Allen, L; MacKay, C; Rigby, M H; Trites, J; Taylor, S M
Abstract: Objective: The Harmonic Scalpel and Ligasure (Covidien) devices are commonly used in head and neck surgery. Parotidectomy is a complex and intricate surgery that requires careful dissection of the facial nerve. This study aimed to compare surgical outcomes in parotidectomy using these haemostatic devices with traditional scalpel and cautery. Method: A systematic review of the literature was performed with subsequent meta-analysis of seven studies that compared the use of haemostatic devices to traditional scalpel and cautery in parotidectomy. Outcome measures included: temporary facial paresis, operating time, intra-operative blood loss, post-operative drain output and length of hospital stay. Results: A total of 7 studies representing 675 patients were identified: 372 patients were treated with haemostatic devices, and 303 patients were treated with scalpel and cautery. Statistically significant outcomes favouring the use of haemostatic devices included operating time, intra-operative blood loss and post-operative drain output. Outcome measures that did not favour either treatment included facial nerve paresis and length of hospital stay. Conclusion: Overall, haemostatic devices were found to reduce operating time, intra-operative blood loss and post-operative drain output.